Evidence for clonal population structure in Escherichia coli. - Ochman, H (1984)
Genotypes of 142 K1 isolates of four O serogroups of Escherichia coli from human hosts in Europe and the United States were characterized by an electrophoretic analysis of allozymic variation in 12 chromosomally encoded enzymes. The genetic structure of natural populations revealed by this analysis is closely similar to that indicated in earlier studies by Achtman and colleagues of the electrophoretic migration pattern for four outer membrane proteins and the chemical structure of the cell-wall lipopolysaccharides. The combined evidence demonstrates that most of the K1 isolates belong to a small number of geographically widespread clones. The distribution of O serogroups among the isolates does not consistently correspond to the clonal structure; O1:K1 isolates represent at least two distantly related, geographically widespread clones, one of which is genetically similar to a clone of the O18:K1 serotype. These findings for K1 isolates add to a growing body of evidence supporting the hypothesis that the genetic structure of natural populations of E. coli is basically clonal, with very limited recombination of chromosomal genes. Clonal structure has important implications for the study of the determinants of pathogenicity and disease specificity in E. coli.